Francisella novicida Two-Component System Response Regulator BfpR Modulates iglC Gene Expression, Antimicrobial Peptide Resistance, and Biofilm Production - Dean, Scott N.; Milton, Morgan E.; Cavanagh, John; van Hoek, Monique L. (Frontiers in Cellular and Infection Microbiology, 2020)
Response regulators are a critical part of the two-component system of gene expression regulation in bacteria, transferring a signal from a sensor kinase into DNA binding activity resulting in alteration of gene expression. In this study, we investigated a previously uncharacterized response regulator in Francisella novicida, FTN_1452 that we have named BfpR (Biofilm-regulating Francisella protein Regulator, FTN_1452). In contrast to another Francisella response regulator, qseB/pmrA, BfpR appears to be a negative regulator of biofilm production, and also a positive regulator of antimicrobial peptide resistance in this bacterium. The protein was crystallized and X-ray crystallography studies produced a 1.8 Å structure of the BfpR N-terminal receiver domain revealing interesting insight into its potential interaction with the sensor kinase. Structural analysis of BfpR places it in the OmpR/PhoP family of bacterial response regulators along with WalR and ResD. Proteomic and transcriptomic analyses suggest that BfpR overexpression affects expression of the critical Francisella virulence factor iglC, as well as other proteins in the bacterium. We demonstrate that mutation of BfpR is associated with an antimicrobial peptide resistance phenotype, a phenotype also associated with other response regulators, for the human cathelicidin peptide LL-37 and a sheep antimicrobial peptide SMAP-29. F. novicida with mutated BfpR replicated better than WT in intracellular infection assays in human-derived macrophages suggesting that the down-regulation of iglC expression in bfpR mutant may enable this intracellular replication to occur. Response regulators have been shown to play important roles in the regulation of bacterial biofilm production. We demonstrate that F. novicida biofilm formation was highly increased in the BfpR mutant, corresponding to altered glycogen synthesis. Waxworm infection experiments suggest a role of BfpR as a negative modulator of iglC expression with de-repression by Mg2+. In this study, we find that the response regulator BfpR may be a negative regulator of biofilm formation, and a positive regulator of antimicrobial peptide resistance in F. novicida.